Molecular analysis of the carbapenem and metronidazole resistance mechanisms of Bacteroides strains reported in a Europe-wide antibiotic resistance survey. - Sóki, József; Eitel, Zsuzsa; Urbán, Edit; Nagy, Elisabeth (Int J Antimicrob Agents, 2013)
Here we examine the carbapenem and metronidazole resistance mechanisms of 640 Bacteroides strains reported in the 2008-2009 European antibiotic susceptibility survey. Of the 22 strains with elevated imipenem minimum inhibitory concentrations (≥4 μg/mL), 10 were cfiA-positive and out of these 5 carried activating insertion sequence (IS) elements in the upstream regions of the cfiA genes. However, resistant strains with cfiA genes but with no activating IS elements were found (n=2) as well as a resistant strain with no cfiA gene. In the former the resistance phenotypes by Etest were heterogeneous, whilst in the latter no carbapenemase production was seen; both mechanisms have been rarely observed, examined and characterised. Interestingly, few (n=3) nim-positive strains were found, including one metronidazole-resistant strain harbouring nimE activated by ISBf6, and two susceptible strains harbouring chromosomally located nim genes.
Keywords: Anti-Bacterial Agents; Bacterial Proteins; Bacteroides; Bacteroides Infections; Carbapenems; DNA Transposable Elements; DNA, Bacterial; Drug Resistance, Bacterial; Europe; Humans; Metronidazole; Microbial Sensitivity Tests; Molecular Sequence Data; Sequence Analysis, DNA